Exploring the Role of NGOs in Women’s Empowerment in Bangladesh - Md. Sobuj Mia; Md. Yeasir Arafat; Md. Ismail Hossen Imran (Penerbit Hellow Pustaka, 2025)
Women’s empowerment is an important issue in the socio-economic context of Bangladesh, which is directly related to the United Nations Sustainable Development Goals (SDGs) 5 and 10, but patriarchal society, poverty, veiling, child marriage, dowry, gender-based discrimination limit the opportunities for women’s empowerment. The objects of this study examine the actual status of women’s empowerment in Bangladesh and the effectiveness of initiatives taken by NGOs in recent decades. Through secondary data, policy reports and descriptive analysis, it examines how NGOs are addressing issues such as gender equality, microfinance, education, skills training, healthcare and legal awareness. The findings show that non-governmental organizations (NGOs) such as BRAC, TMSS, Proshika, UNDP, ASA, Bangladesh Mahila Parishad have been working towards women’s political, economic, social and educational empowerment through initiatives such as microfinance programmed, skill development, education, healthcare and legal awareness. Despite their success, NGOs face challenges including patriarchal practices, child marriage, poverty, debt traps and difficulties in coordinating with government agencies. The study provides practical suggestions for enhancing collaboration with the government, awareness-raising campaigns, ensuring the presence of local resources, skills training programmed, incentives in the education sector, providing soft loans, implementing laws to prevent child marriage, dowry and violence, ensuring a women-friendly environment and quotas in the workplace, and increasing women's direct participation in decision-making. Overall, this study provides clear insights for NGOs, policymakers and other stakeholders to ensure women's empowerment.